Basic safety measures and management of residues of material collected for papanicolaou exam - Nancy Costa de Oliveira; Escolástica Rejane Ferreira Moura (Rev Rene)
The basic safety measures to prevent infection and the management of health services residues are budding issues regarding the safety of health workers, customers and the environment. The aim of this study was to investigate the use of basic safety measures in preventing infections and the management of the residues in the material collected for Papanicolaou exam. The data have been collected in 21 (100%) family health divisions in Maraguape, Ceará. It was done through direct structured and participative observation by the nurses. Such nurses did not use to wash their hands during the Papanicolaou exam, however, the latex gloves were guaranteed in all divisions and they were also used in 100% of the exams. The possessing of contaminated reusable items and managing of infected residuals showed to be inappropriate to what we recommend to be implanted according to the Resolution of the Diretoria Colegiada (RDC number 306/2004) of the National Agency of Sanitation Surveillance.